ANALISIS ASPEK SOSIAL EKONOMI PETANI PADI PESERTA PROGRAM PENCETAKAN SAWAH BARU - Nurhana, Nurhana; Rukka, Ruli M.; Sari, Pipi Dian; Rukmana, Didi; Bulkis, Sitti; Bakri, Rasyida (Jurnal Sosial Ekonomi Pertanian, 2019)
The strategy to increase rice production to support national food security is realized through a rice field construction program. The rice field construction program aims to increase the area of rice fields through the expansion of rice fields. This study aims to: 1) Describe the farming profile before and after the rice field construction program in Botto Village, Pitu Riase District, Sidrap Regency, 2) Analyze changes in socio-economic aspects of participating farmers before and after the rice field construction program in Village Botto , Pitu Riase District, Sidrap Regency. The population of the study were all farmers who participated in the Rice Field Construction Program, which were 51 people using the entire population census method to become respondents. The analytical method used is quantitative descriptive analysis. The results of the study concluded that: 1) The rice field construction program in Botto Village, Pitu Riase Subdistrict, Sidrap Regency changed the farming profile in terms of non-productive land area and used, function and land use, cultivated species, ownership status and land tax. Utilization of human resources, equipment resources, financial resources and conditions of supporting facilities, 2) The rice field construction program provides socio-economic changes to the communities in Botto Village in the form of labor use, increased interaction among farmers, changes in livelihood status and increased income.